Industrial processing versus home processing of tomato sauce: Effects on phenolics, flavonoids and in vitro bioaccessibility of antioxidants - Tomas, Merve; Beekwilder, Jules; Hall, Robert D.; Sagdic, Osman; Boyacioglu, Dilek; Capanoglu, Esra (ELSEVIER SCI LTD, 2017)
The effect of industrial and home processing, in vitro gastrointestinal digestion, individual phenolic content, and antioxidant capacity of tomato into tomato sauce were investigated. Industrial processing of tomato fruit into sauce had an overall positive effect on the total antioxidant capacity (similar to 1.2-fold higher) compared to tomato fruit whereas home processing of tomato fruit into sauce led to a decrease in these values. Untargeted LC-QTOF-MS analysis revealed 31 compounds in tomato that changed upon processing, of which 18 could be putatively identified. Naringenin chalcone is only detectable in the fruit, while naringenin is strongly increased in the sauces. Rutin content increased by 36% in the industrial processed sauce whereas decreased by 26% in the home processed sauce when compared to fruit. According to the results of an in vitro gastrointestinal digestion model, industrial processing may lead to enhanced bioaccessibility of antioxidants. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Tomato sauce; Processing; Antioxidant; Bioavailability; In vitro gastrointestinal digestion; BIOACTIVE COMPOUNDS; FOOD; LYCOPENE; OIL; ISOMERIZATION; DEGRADATION; POLYPHENOLS; CAPACITY; COOKING; Chemistry; Food Science & Technology; Nutrition & Dietetics